2003
DOI: 10.1021/jp035491z
|View full text |Cite
|
Sign up to set email alerts
|

The Measure of TiO2 Photocatalytic Efficiency and the Comparison of Different Photocatalytic Titania

Abstract: The dependence of hydroxyl radical yield on the substrate concentration, pH, oxygen concentration, and light intensity, using different TiO 2 preparations, was investigated. The quantum yields of formaldehyde and carbon dioxide, obtained with the aid of an integrating sphere in the methanol and formate systems, respectively, were used to derive the primary yield of hydroxyl radicals. The limiting yield of • OH ads , achieved at high scavenger concentrations, is independent of the nature of the scavenger (metha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 73 publications
5
62
1
2
Order By: Relevance
“…Comparisons of "apparent quantum efficiencies" are only meaningful if effects due to light scattering and penetration are comparable.) The pH trend and the "apparent quantum efficiency" obtained in this study is similar to what has been reported in previously published works [50,51], where methanol was used as general OH radical probe with a very low tendency to be adsorbed on TiO 2 surfaces. However, our "apparent quantum efficiency" is at variance with the much smaller value reported by Hirakawa et al [26].…”
Section: Effects Of Added Phosphate and Fluoride Anionssupporting
confidence: 89%
“…Comparisons of "apparent quantum efficiencies" are only meaningful if effects due to light scattering and penetration are comparable.) The pH trend and the "apparent quantum efficiency" obtained in this study is similar to what has been reported in previously published works [50,51], where methanol was used as general OH radical probe with a very low tendency to be adsorbed on TiO 2 surfaces. However, our "apparent quantum efficiency" is at variance with the much smaller value reported by Hirakawa et al [26].…”
Section: Effects Of Added Phosphate and Fluoride Anionssupporting
confidence: 89%
“…In aqueous medium, O 2 •2 in turn produces highly reactive species, such as HO • and HO 2 • , which also oxidize the organics. Water is adsorbed on the semiconductor, both molecularly and dissociatively [2,3]; hole-trapping by either the surface hydroxyl group or water molecule results in short-lived HO • radicals, which are the primary oxidizing agents [4][5][6][7]. Reports on the photodegradation of phenol are numerous and TiO 2 in different modifications [8][9][10], including metal-doped [8] and dye-sensitized TiO 2 [11], ZrO 2 [12], MoO 3 [10,12], MoS 2 [13], WO 3 [9], WS 2 [14], PW 12 O 40 3- [15], a-Fe 2 O 3 [10,15], CuO [10], GdCoO 3 [16], ZnO [9,10], ZnS [10], CdO [10], CdS [9,10], CdSe/TiO 2 [17], In 2 O 3 /TiO 2 [18], SnO 2 [13], Bi 2 O 3 [10], Sb 2 O 3 [10], and CeO 2 [10], are the semiconductors used as a catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…• OH radical are indistinguishable and refer both as hole without discrimination, although in some cases the term localized or trapped hole is implicitly used for • OH ads [47,49]. Hole is quickly converted to…”
Section: Mechanismmentioning
confidence: 99%